Ed Emberley's Picture pie : a circle drawing book. - Emberley, Ed. (Boston : Little, Brown, 1984)
Shows how to cut a basic circle into arcs and curves and use the pieces to draw birds, animals, snowmen, fish, and many other objects and designs.
Wilson's Children.
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
K-3
Keywords: Circle in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Circle in art; Drawing -- Technique; Circle in art; Drawing -- Technique; Circle; Rectangle; Triangle